Cellulolitic Activities Of Actinomycetes Isolated From Soil Rhizospere of Waigeo, Raja Ampat, West Papua - Nurkanto, Arif (JOURNAL OF TROPICAL SOILS, 2009)
Seven actinomycetes isolated from Waigeo’s soil rhizospere have been characterized in growth, cellulase activities and pH. These actinomycetes were chosen based on their capabilities in cellulose degradation which were recognized by previous study. Those isolates are belonging to Streptomyces and Actinoplanes genera based on morphological and molecular analyses. The growths of actinomycetes were investigated based on spectrophotometric approach and cellulase activities were conducted based on reduction sugar. Cellulase activities, cell growth, and pH had significant correlation based on statistical analysis.  The highest enzyme activities was acquired from  Streptomyces bobili LIPIMC-A-283 (0,519 µmol mL-1 minute-1) at 96 h of incubation. This study provided important basic information on potential cellulolitic alternative from actinomycetes group, as consideration on choosing low-cost technique using microbial agent in cellulose treatment.